Pengaruh Motivasi Terhadap Kinerja Aparatur Sipil Negara Pada Dinas Satuan Polisi Pamong Praja Dan Pemadam Kebakaran Kabupaten Enrekang. - Yasser, Yasser; Hakim, Lukman; Tahir, Nurbiah (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2020)
This study aimed to find out how the work motivation and performance of employees in the Civil Service Police Unit and the Enrekang District Fire Department and to find out how much influence motivation on the performance of employees in the Office. The method used in this study was a quantitative method using statistical formula to help process data and analyze data obtained from the results of the study by distributing questionnaires / questionnaires as many as 40 questionnaires to 25 Satpol employees and 15 Damkar employees with a total of 40 respondents. This study used a simple linear regression formula to find out whether there was a relationship between motivation and performance, then proceed with the determination coefficient to determine the results of the effects caused. The results showed that motivation had a relatively moderated relationship with employee performance. Based on the analysis results that had been described then Motivational variables significantly influence employee performance variables in the Civil Service Police Unit and Enrekang District Fire Department.